1997
DOI: 10.1007/s004240050363
|View full text |Cite
|
Sign up to set email alerts
|

ANP gene expression in rat hearts during hypoxia

Abstract: It is unclear whether the increase in plasma atrial natriuretic peptide (ANP) concentration during hypoxia is due to direct, hypoxia-induced upregulation of ANP secretion in the heart, or to pressure overload of the right ventricle (RV) following hypoxia-induced pulmonary hypertension. To test the hypothesis that hypoxia leads to an early upregulation of the ANP gene, we examined the influence of acute and prolonged inspiratory hypoxia (6 h, 1 or 3 weeks) on the expression of ANP messenger ribonucleic acid (mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Experimental groups and chronic hypoxia. Adult male Wistar rats (250-300 g; Charles River, Sulzfeld, Germany) were randomly assigned to one of the following groups: normoxia and plain water from Rats were exposed to normobaric hypoxia (10% O 2 -90% N 2 ) in transparent plastic chambers as previously described (20). Relative humidity within the chamber was kept at Ͻ70% with anhydrous CaSO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental groups and chronic hypoxia. Adult male Wistar rats (250-300 g; Charles River, Sulzfeld, Germany) were randomly assigned to one of the following groups: normoxia and plain water from Rats were exposed to normobaric hypoxia (10% O 2 -90% N 2 ) in transparent plastic chambers as previously described (20). Relative humidity within the chamber was kept at Ͻ70% with anhydrous CaSO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the study period, right ventricular systolic pressure (RVSP) was measured in all rats with a closed-chest technique as previously described (20). For this purpose, each rat was taken from its cage and immediately anesthetized with thiopental sodium (50 mg/kg ip).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental and clinical studies showed that during chronic hypoxia, right heart ANP and BNP synthesis and circulating NP levels increase, possibly in response to the RV pressure overload provoked by pulmonary vasoconstriction [ 9 – 11 , 44 ]. Because synthetic ANP counterregulates hypoxic pulmonary vasoconstriction [ 8 , 22 , 26 ] and limits the interaction of endothelial and inflammatory cells [ 25 , 39 ] and the proliferation of cultured vascular SMC [ 24 ], it was proposed that enhanced endogenous ANP/BNP release helps to mitigate the development of hypoxic PH [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…CA itself stimulates the a 1 -adrenergic receptor and then up-regulated h-MHC mRNA expression and, thereby, myocardial hypertrophy (Waspe et al, 1990;Kariya et al, 1993Kariya et al, , 1994Morkin, 2000). Furthermore, h-MHC mRNA expression is up-regulated under certain conditions, including pressure overload and hypoxia (Gupta and Gupta, 1997;Pissarek et al, 1997;Wong et al, 1997;Pfeifer et al, 1997;Morkin, 2000;Joseph et al, 2000). It may be that the decrease in the plasma levels of progesterone indicated an impairment of the functions of the placenta, and that fetal hypoxia occurred.…”
Section: Discussionmentioning
confidence: 91%